The cost disadvantage of steep slope viticulture and strategies for its preservation - Larissa Strub; Simone Mueller Loose (OENO One, 2021)
The falling fallow of steep slope vineyards is caused by cost disadvantages that have not been analysed so far. This study quantified the production costs of different types of steep slopes, identified cost drivers within viticultural processes and assessed the impact of grape yield on the production cost for vertical shoot positioning (VSP) systems. It also examined under what conditions the reshaping of steep slope vineyards into transversal terraces (TTs) is economically viable. Costs were derived from a dataset of 2321 working time records for labour and machine hours from five German wine estates over three years. The costs for standard viticultural processes were compared across five site types with different mechanisation intensities by univariate analysis of variance with fixed and random effects. The net present value (NPV) of reshaping slopes into horizontal terraces was also assessed. Manual management of steep slopes was determined to be 2.6 times more costly than standard flat terrain viticulture. The cost disadvantage of steep slopes mainly stems from viticultural processes with limited mechanisability that require specialised equipment and many repetitions. Current subsidies fall short of covering the economic disadvantage of manual and rope-assisted steep slopes. Climate change-related drought and yield losses further increase the economic unsustainability of steep slopes. Under certain conditions, the transformation of manual steep slope sites into TTs can be a viable economic option. Strategies to reduce the cost disadvantage are outlined. The estimated cost benchmarks provide critical input for steep slope wine growers’ cost-based pricing policy. These benchmarks also give agricultural policy reliable indicators of the subsidies required for preserving steep slope landscapes and of the support needed to transform manual steep slope sites into TTs.